Analysis of Budget Utilization Efficiency in Public Schools in Mahakam Ulu - Batang, Samson; Abeh, Yohanes Andy; Wan, Markus; Wibawa, Radhitya; Mebang, Desi Natalia; Warman, Warman; Mulawarman, Widyatmike Gede; Fitriadi, Ahmad (Lembaga Riset Mutiara Akbar, 2025)
The efficiency of education budget utilization in public schools in Mahakam Ulu is a crucial aspect in ensuring optimal learning quality. This study aims to analyze the effectiveness of education budget management, identify existing challenges, and formulate strategies to enhance budget efficiency in public schools in the region. A qualitative descriptive approach was used in this research, with data collected through in-depth interviews, observations, and document analysis. The findings reveal that budget planning has been carried out collaboratively, involving various stakeholders. However, challenges persist in terms of data accuracy, delays in fund disbursement, and complex administrative regulations. Additionally, the allocated budget is not always sufficient to meet operational needs, particularly in facility procurement and teacher welfare. Indications of budget inefficiencies were identified, particularly in programs that do not significantly impact education quality. Although most schools have implemented transparent and well-documented financial recording systems, limited administrative capacity and infrastructure remain major obstacles in financial reporting and budget management. To improve budget efficiency, schools have begun implementing strategies such as needs-based budgeting, digital financial management, zero-based budgeting, and exploring alternative funding through partnerships with the private sector and local communities. This study recommends more flexible policy support from local governments and the Education Office, enhanced administrative capacity in school financial management, and the implementation of a performance-based funding model to ensure that every budget allocation directly contributes to improving education quality. With more transparent, flexible, and data-driven budget management, education in Mahakam Ulu is expected to continue developing and providing greater benefits to students and the community